OPA1 Modulates Mitochondrial Ca2+ Uptake Through ER-Mitochondria Coupling - Cartes-Saavedra, Benjamín; Macuada, Josefa; Lagos, Daniel; Arancibia, Duxan; Andrés, María E.; Yu-Wai-Man, Patrick; Hajnóczky, György; Eisner, Verónica (Frontiers in Cell and Developmental Biology, 2022)
Autosomal Dominant Optic Atrophy (ADOA), a disease that causes blindness and other neurological disorders, is linked to OPA1 mutations. OPA1, dependent on its GTPase and GED domains, governs inner mitochondrial membrane (IMM) fusion and cristae organization, which are central to oxidative metabolism. Mitochondrial dynamics and IMM organization have also been implicated in Ca2+ homeostasis and signaling but the specific involvements of OPA1 in Ca2+ dynamics remain to be established. Here we studied the possible outcomes of OPA1 and its ADOA-linked mutations in Ca2+ homeostasis using rescue and overexpression strategies in Opa1-deficient and wild-type murine embryonic fibroblasts (MEFs), respectively and in human ADOA-derived fibroblasts. MEFs lacking Opa1 required less Ca2+ mobilization from the endoplasmic reticulum (ER) to induce a mitochondrial matrix [Ca2+] rise ([Ca2+]mito). This was associated with closer ER-mitochondria contacts and no significant changes in the mitochondrial calcium uniporter complex. Patient cells carrying OPA1 GTPase or GED domain mutations also exhibited altered Ca2+ homeostasis, and the mutations associated with lower OPA1 levels displayed closer ER-mitochondria gaps. Furthermore, in Opa1-/- MEF background, we found that acute expression of OPA1 GTPase mutants but no GED mutants, partially restored cytosolic [Ca2+] ([Ca2+]cyto) needed for a prompt [Ca2+]mito rise. Finally, OPA1 mutants’ overexpression in WT MEFs disrupted Ca2+ homeostasis, partially recapitulating the observations in ADOA patient cells. Thus, OPA1 modulates functional ER-mitochondria coupling likely through the OPA1 GED domain in Opa1-/- MEFs. However, the co-existence of WT and mutant forms of OPA1 in patients promotes an imbalance of Ca2+ homeostasis without a domain-specific effect, likely contributing to the overall ADOA progress.